2020
DOI: 10.3389/fonc.2020.575366
|View full text |Cite
|
Sign up to set email alerts
|

Prp19 Is an Independent Prognostic Marker and Promotes Neuroblastoma Metastasis by Regulating the Hippo-YAP Signaling Pathway

Abstract: Pre-mRNA processing factor 19 (Prp19) was previously reported to be involved in tumor progression. However, Prp19 expression and its functions remain elusive in neuroblastoma. Here, we aim to identify the functions and mechanisms of Prp19 in neuroblastoma. Neuroblastic tumor tissue microarrays and two independent validation data sets indicate that Prp19 is associated with high-risk markers and bone marrow metastasis and serves as a prognostic marker for worse clinical outcomes with neuroblastoma. Gain-and loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Hence, they suggested USP39 as an oncogenic factor that can play a pivotal role in human RCC treatment. Moreover, pre-mRNA processing factor (PRPF) 4B kinase 50 , pre-mRNA processing factor 19 (PRP19) 51 , 52 , and pre-mRNA processing factor 31 (PRP31) 53 are the other oncogenic factors that are involved in mRNA processing pathway. Furthermore, the central role of the factors mentioned above is reported in previous studies in invasiveness and metastatic of numerous malignancies, including prostate cancer, melanoma, hepatocellular carcinoma, and invasive ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, they suggested USP39 as an oncogenic factor that can play a pivotal role in human RCC treatment. Moreover, pre-mRNA processing factor (PRPF) 4B kinase 50 , pre-mRNA processing factor 19 (PRP19) 51 , 52 , and pre-mRNA processing factor 31 (PRP31) 53 are the other oncogenic factors that are involved in mRNA processing pathway. Furthermore, the central role of the factors mentioned above is reported in previous studies in invasiveness and metastatic of numerous malignancies, including prostate cancer, melanoma, hepatocellular carcinoma, and invasive ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of PRP19 in lung cancer cells also decreased cisplatin-induced and impaired cell migration and tumor growth [ 153 ]. Contrastingly, PRP19 expression correlated with bone marrow metastasis in neuroblastoma and was an overall adverse prognostic biomarker with a positive effect on cell migration [ 154 ]. Unanimously, however, work from many labs over the years has shown that depletion of NTC and PRP19-associated complexes is clearly detrimental to cancer cell resistance to genotoxic stress, and thus PRP19 inhibition could potentially improve the efficacy of treatment regimens by enhancing cell death and/or senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Other poor prognostic biomarkers are limited to the aggressive profile of neuroblastomas, not ganglioneuroma. T hese include epit helia l-mesenchyma l t ra nsition (EMT)-related pre-mRNA processing factor 19 (Prp19) (56). The Bcl-2 gene, related to programmed cell death, encodes an oncoprotein that has been suggested to help the differentiation between ganglioneuroma/neuroblastoma based on Bcl-2 immunostaining, but currently it is not considered a relevant prognostic marker (57).…”
Section: Advanced Biomarkersmentioning
confidence: 99%